2009
DOI: 10.1007/s00775-009-0565-x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoenzymatic dealkylation of alkyltins by biological dithiols

Abstract: We investigated the time dependence of the degradation of three alkyltin derivatives by a nine amino acid linear peptide (I1LGCWCYLR9) containing a CXC motif derived from the primary sequence of stannin, a membrane protein involved in alkyltin toxicity. We monitored the reaction kinetics using the intrinsic fluorescence of the tryptophan residue in position 5 of the peptide and found that all of the alkyltins analyzed are progressively degraded to dialkyl derivatives, following a pseudo-enzymatic reaction mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…snn was originally identified as a cDNA specifically expressed in TMT-sensitive tissues such as hematopoietic organs and immune system lineages [ 57 ]. Subsequent studies showed binding of TMT to Stannin [ 58 60 ] and of Stannin to 14-3-3ζ [ 44 ]. Although the molecular and cellular consequences of such binding and the roles of Stannin in TMT toxicity and under normal physiology have not been fully elucidated, several results might suggest a relationship with PI metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…snn was originally identified as a cDNA specifically expressed in TMT-sensitive tissues such as hematopoietic organs and immune system lineages [ 57 ]. Subsequent studies showed binding of TMT to Stannin [ 58 60 ] and of Stannin to 14-3-3ζ [ 44 ]. Although the molecular and cellular consequences of such binding and the roles of Stannin in TMT toxicity and under normal physiology have not been fully elucidated, several results might suggest a relationship with PI metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…TBT was reported to preferentially bind to dithiols and to establish a stable tetrahedral structural arrangement with the protein structure after debutylation through the formation of covalent bonds between tin and two sulfur atoms. [21,[39][40][41] On this basis, the possible presence of dithiol targets on F 1 F O -ATPase was checked by using both hydrophilic and hydrophobic MTR so as to covalently block isolated -SH groups and to prevent possible bifunctional TBT binding by creating sulfur-tin-sulfur bridges. Either hydrophilic (mersalyl acid and DTNB) or hydrophobic (NEM) MTR was used.…”
Section: Tbt Interacts With Individual Thiolsmentioning
confidence: 99%